Rapid Visco Analyzer Measurements of japonica Rice Cultivars to Study Interrelationship between Pasting Properties and Farming System - Amit Kesarwani; Po Yuan Chiang; Shih Shiung Chen (International Journal of Agronomy)
Rheological properties influence the starch softness and cooking quality. Two japonica rice cultivars were studied that were cultivated under organic and conventional farming. Study was conducted for 2 years in popular japonica cultivars, that is, Kaohsiung number 139 and Taikeng number 16, which were grown twice a year in Taiwan. The results highlighted that major pasting properties such as peak viscosity, setback value, and pasting temperature improved under organic farming; however, in further analysis, eating and cooking quality reported no significant changes except aroma in rice.